2021
DOI: 10.3389/fcell.2020.630147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of LH Action on Breast Cancer Cell Migration and Invasion via Kinase and Scaffold Proteins

Abstract: Breast cancer (BC) is a major public health problem affecting women worldwide. Approximately 80% of diagnosed cases are hormone-dependent breast cancers. These hormones are known to stimulate tumor development and progression. In this setting, tentative evidence suggests that luteinizing hormone (LH) may also play a role in tumors. In BC cells that express functional LH receptors (LHR), this hormone regulates cell migration and invasion by controlling several kinases that activate actin cytoskeletal proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…In this context, preliminary data point to a potential function for LH in tumorigenesis. This hormone controls cell migration and invasion in BC cells that exhibit functional LH receptors (LHR) [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…In this context, preliminary data point to a potential function for LH in tumorigenesis. This hormone controls cell migration and invasion in BC cells that exhibit functional LH receptors (LHR) [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…This process is initiated through rapid extragonadal LHCGR signalling to Src/ FAK/paxillin resulting in the phosphorylation/activation of the nucleation promoter factors cortactin and N-WASP. As a result, there is an increase in cell motility and the invasive properties which promote the tumour cell metastatic dissemination 60 .…”
Section: Lhcgr Expression In Cancermentioning
confidence: 99%
“…In general, ARPs have numerous crucial biological functions, involving regulation of cell differentiation, migration, adhesion, as well as cargo transport [22,23]. Recent studies have demonstrated that ARPs are associated with malignant behavior in colorectal, breast and lung cancers and that they act in promoting cancer cell invasion and metastasis [24][25][26][27][28][29]. Liu et al recently discovered that ARPC1B in macrophages promoted motility and epithelial-mesenchymal transition (EMT) of glioma cells [30].…”
Section: Introductionmentioning
confidence: 99%